Peran Guru Pendidikan Agama Kristen dalam Membangun Kerohanian Siswa SMK Paulus Palalangon - Christian Army Panjaitan; Fadila Ventine Simbala; Moresta Harianja (STT INTI Bandung, 2025)
This study aims to examine the strategic role of Christian Religious Education (PAK) teachers in the context of Christian education at SMK Paulus Palalangon. The focus of the study includes three important aspects: (1) PAK teachers as role models in students' spiritual growth, (2) The urgency of using interesting and relevant learning media to support understanding of Christian values, and (3) The concrete role of PAK teachers in fostering students' spiritual life in the SMK Paulus Palalangon environment. This study uses a qualitative approach with library research and survey methods as the basis for data collection and analysis. This study states that teacher exemplars in spiritual life have a significant impact on students' spiritual development. In addition, the use of contextual and innovative learning media also strengthens the effectiveness of teaching Christian values. This study recommends strengthening the capacity of PAK teachers as inspiring educators and spiritual guides in the SMK Paulus Palalangon environment.